An Audit Of Kidney Biopsy Findings In A Tertiary Care Nephrology Department: 2010-2013. - Sabir, Omer; Rizvi, Nabiha; Tarif, Nauman; Riaz, Muhammad Mohsin; Rafique, Kashif; Rizvi, Nabiha; Qadri, Ghulam Abbas (Pakistan Journal of Kidney Diseases, 2021)
Renal biopsy, although an invasive procedure, still remains the last court of appeal in patients with clinical suspicion of glomerulonephritis. In most of the cases it will establish the diagnosis, stage the disease and provides information about the potential therapeutic modalities that can be employed. We report our experience with renal biopsy in our tertiary care setup. A comparison with local and international data will follow. METHODS: This was a retrospective analysis of renal biopsies conducted at Department of Nephrology, Fatima Memorial Hospital in the period between February 2010 to August 2013 (three years and 6 months). RESULTS: During the period between February 2010 and October 2013, a total of 260 biopsies were conducted on the native kidneys. There were 137 (52.5%) females and 124 males (47.5%). The mean age was 31.40 + 13.63 years (median: 28 years, range: 3 – 77 years). In all patients at least two cores were taken. 22 (8.5%) biopsies failed to yield glomeruli sufficient to make a diagnosis. Mean number of glomeruli obtained were 12.29 + 7.72 (median: 10, range: 1 – 46). Out of the total cohort 38.3% (n=100) had PGD, 48.3% (n=126) had SGD and rest of the patients (5%; n=10) had other diagnoses. CONCLUSIONS: The renal biopsy findings in our centre are similar to those reported elsewhere internationally.